Caracterização da fadiga mecânica de baixo ciclo em ligas superelásticas de NiTi - Ana Maria Gontijo Figueiredo (2006)
The continuous growth of the use of superelastic alloys, especially those of the Ni-Ti system, in medical and odontologic applications, together with the growing trend to less invasive procedures, have imposed an ever growing need for the investigation of the production technology and performance of those materials. As, in most applications, these materials are subjected to cyclic mechanical loads, the knowledge of their fatigue behavior is fundamental to their safe use. However, the non linear characteristics of superelasticity make the classic theories inadequate to model the mechanical behavior of materials that present such property. Therefore, many aspects of the behavior of these materials are still controversial. The present investigation focuses the low-cycle fatigue behavior of NiTi wires subjected to deformation-control rotation-bending conditions. Five wires - one with a microstructure of stable austenite, two superelastic, one with a microstructure of austeniteand martensite (dual phase), and one martensitic - were used. An austenitic stainless steel wire was also tested for comparison. Fatigue a-Nf curves were obtained and compared to results available in the literature. It was observed that, for the conditions tested, fatigue lifeof the martensitic wires is the longest. Numerical modeling by the finite element method suggested that deformation and stress concentration was much less intense in martensite and it is proposed that this may contribute to the longer fatigue life of the martensitic wire. The microstructure of the wires was characterized both before and after the fatigue testing. It was shown that the superelastic and dual phase wires present fatigue curves that, for deformation below 4%, are close to that of the austenitic wire. However, for higher deformation, their fatigue curves tend to approach that of the martensitic wire. This causes, for those wires, an increase of fatigue live, resulting in unexpected Z-shaped curves. It is shown that the changes in the Z segment of fatigue curves are related to the relative stability of the austenite in the wires. Furthermore, this Z effect can also be linked to changes in the fatigue fracture surface and crack morphologies. It is proposed that sucheffect is caused by the inhibition of martensite formation at the crack tip by the volume reduction associated to the transformation. This inhibition is overcame for higher imposed deformation, and an ever increasing volume of martensite is formed in the material that makes it more difficult for the nucleation and growth of fatigue cracks.